Coupled analysis of integrated dynamic responses of side-by-side offloading FLNG system. (15th November 2018) - Zhao, Dongya; Hu, Zhiqiang; Zhou, Ke; Chen, Gang; Chen, Xiaobo; Feng, Xingya
Abstract: Integrated dynamic responses of FLNG system in side-by-side offloading operation are investigated numerically and experimentally in this paper. A numerical code is developed based on potential flow theory to predict the interactions between connected vessels' motions and liquid sloshing in the time domain. The impulsive response function (IRF) method is adopted in the resolution for 6 DOF vessels' motions, nonlinear sloshing in liquid tanks is solved using boundary element method (BEM), and connection system including hawsers and fenders is numerically modeled as linear response system. A series of model tests are conducted to validate the feasibility of the numerical code. Hydrodynamic interaction between the vessels and shielding effects under different wave directions are analyzed; sloshing effects on the vessels' motions and on the loads of connection system are investigated; the sensitivities of the vessels' motions and loads to connection system stiffness are discussed. It is found that the vessels' motions are significantly affected by the hydrodynamic interactions between vessels and sensitive to wave directions for shielding effects. The radiation forces of the adjacent vessel tend to amplify vessel's motions and LNG carrier is more likely to be affected by FLNG's radiation forces for their difference in displacement. In addition, compared with solid loading condition, liquid loading vessel tends to have decreased natural roll frequency and have increased sway motions in the frequency region that higher than the natural sloshing frequency. The two sloshing responses peaks appear in the natural roll frequencies and natural sloshing frequencies, which are respectively mainly excited by vessels' roll and sway motions. Besides, in low fill conditions, the sloshing loads contribute to larger sway motions in low fill conditions for the natural sloshing frequencies are closer to the main response frequency region of vessels. Sloshing nonlinearity gets obvious in the conditions with low fill conditions and large wave amplitude, while the motion responses of vessels have slight nonlinearity with the increases of sloshing nonlinearity when no violent sloshing with wave break is excited. Furthermore, small stiffness of the connection system has slight influences on the vessels' motions, and resonant motions can be excited when the natural frequency of the connection system located in the wave frequency region. Highlights: A numerical code is developed to predict the integrated dynamic responses in side-by-side offloading FLNG system. Experimental tests are conducted to validate the numerical code. Comparative studies are carried out to investigate the coupling mechanism. The effects of filling levels and wave directions on FLNG performances are investigated.